The antioxidative components from Alpinia nutans - Mohamed, Habsah; Lajis, Md. Nordin; Ali, Abdul Manaf; Md. Sukari, Mohd Aspollah; Yap, Taufiq Yun Hin; Kikuzaki, Hiroe; Nakatani, Nobuji (Swets & Zeitlinger, 2003)
The methylene chloride extract of Alpinia nutans was investigated for its antioxidant constituents. 5,6-Dehydrokawain (1), flavokawin-B (2), 1,7-diphenyl-5-hydroxy-6-hepten-3-one (3), (-)-pinocembrin (4) and a mixture of stigmasterol and β-sitosterol were isolated. The antioxidant activity was measured on isolates 1-4 using ferric thiocyanate (FTC) and diphenylpicrylhydrazyl (DPPH) free radical scavenging techniques.